Brain computation as hierarchical abstraction - Ballard, Dana H. (Dana Harry), 1946- (Computational neuroscience., 2015)
The vast differences between the brain's neural circuitry and a computer's silicon circuitry might suggest that they have nothing in common. In fact, as Dana Ballard argues in this book, computational tools are essential for understanding brain function. Ballard shows that the hierarchical organisation of the brain has many parallels with the hierarchical organisation of computing; as in silicon computing, the complexities of brain computation can be dramatically simplified when its computation is factored into different levels of abstraction.